Food security in Kenya: Insights from a household food demand model - Lilian Korir; Marian Rizov; Eric Ruto (Economic Modelling, 2020)
This paper evaluates the household food security situation in Kenya in terms of access to food. We apply a quadratic almost ideal demand system (QUAIDS) model to nationally representative household survey data from Kenya, and estimate and interpret price and expenditure elasticities as indicators of household sensitivity to market shocks. Our estimation results show positive expenditure elasticities, close to unity, while all compensated and uncompensated own-price elasticities are negative and smaller in magnitude. A complementary welfare analysis shows high compensated variations in the long run, ranging between 34% and 131% across food groups. This suggests that rising relative food costs have led to deterioration of the food security situation in Kenya, and the most severely affected households seem to be those that rely on informal markets and reside in rural areas. To improve food security, targeted income support could be a more effective policy than price support, given the much higher estimated expenditure elasticities.
Keywords: D12; I12; O55; Q18; C31; 330; Food security; Food demand; QUAIDS; Expenditure and price elasticity; Welfare; Kenya